The Relationship between Sleep Quality and Smartphone Addiction among Adolescents - Duygu Arıkan; Nazan Gürarslan Baş; Fatma Kurudirek (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Technological developments have increased the usage of mobile equipment. Using a smartphone became a part of life and accentuated its usage day aftr day especially in adolescent groups.Aim: The study was aimed to examine the relationship between sleep quality and smartphone addiction of adolescents.Method: This cross-sectional study was carried out with 1192 high school students between March and June 2019. Data were collected with the Personal Information Form, Pittsburg Sleep Quality Index, Smartphone Addiction Scale. The data were evaluated through percentile distributions, means, independent samples t-test, Kruskal-Wallis test, ANOVA, and Pearson correlation analyses.Results: The mean age of adolescents was determined to be 15.79 ± 0.96, with the mean total score of the Pittsburg Sleep Quality Index was 6.05 ± 3.04 and the Smartphone Addiction Scale was 36.01 ± 10.82. Statistically signifiant diffrences were observed among adolescents concerning gender, grade, daily smartphone usage duration, internet accessibility, and the use of smartphones before bedtime, impacting both sleep quality and smartphone addiction (p lt; 0.05). A positive and meaningful correlation was found between sleep quality and smartphone addiction in adolescents (p lt; 0.05).Conclusion: As the smartphone addiction increases, sleep quality decreases. Adequate sleep is crucial during the growth spurt period. It is evaluated that early diagnosis and prevention of smartphone addiction in adolescents could make a signifiant contribution to the protection and promotion of adolescent health.